AKSELARASI PENINGKATAN KAPASITAS MAHASISWA FOSSEI SULSELBARTA & MALUKU MELALUI KOMPETISI KARYA TULIS ILMIAH SHARIA BUSINESS PLAN - Hamizar, Arizal; Wakano, Abidin; Maruapey, Muammar W; Yaman, Afdhal; Hatala, Siti K; Putri; Damapolii, Finanti G; Anas, Alfiah A; Diman, Agus P (MAJU : Indonesian Journal of Community Empowerment, 2024)
The Sharia Business Plan competition aims to enhance students' competence in the field of Islamic economics. Students are encouraged to develop business ideas based on Sharia principles that are relevant to market needs. The event will be held from June 15-20, 2024, at IAIN Ambon, consisting of several stages, including participant registration, a national seminar, desk evaluation, and business idea presentations in the semifinals and finals. The results of the event showed high enthusiasm and quality from the participants. The top three teams advanced to the finals with innovative and practical business ideas. The winning team was able to present a strong, relevant business concept with real implementation potential. Overall, the event successfully strengthened students' understanding of Islamic economics and prepared them to actively engage in the development of Islamic economics in the future.